Modern weapons and military equipment for issue 2-2020 - Vučković, Dragan (Vojnotehnički glasnik / Military Technical Courier, 2020)
This Is How Poland Would Stop A Russian Invasion (Could Warsaw Win?);Study This Picture: Meet Japan's Mitsubishi X-2 Shinshin Stealth Fighter.